Surface lithium abundance distribution and magnetic field for four roAp stars - Polosukhina, N.; Shulyak, D.; Shavrina, A.; Lyashko, D.; Drake, N.A.; Glagolevski, Yu.; Smirnova, M.; Kudryavtsev, D. (Известия Крымской астрофизической обсерватории, 2013)
High-resolution spectra obtained with the 6-m BTA telescope, Russia, and with HARPS and VLT/UVES telescopes at ESO, Chile, were used for Doppler Imaging analysis of two roAp stars, HD 12098 and HD 60435, showing strong and variable Li resonance line in their spectra. We found that Li has highly inhomogeneous distribution on the surfaces of these stars. We compared our results with previously obtained Doppler Imaging mapping of two CP2 stars, HD 83368 and HD 3980, and discuss correlation between the position of high Li-abundance spots and magnetic field.